Somatic BRCA Mutation in High Grade Epithelial Ovarian Cancer Patients - Manchana, Tarinee; Lertkhachonsuk, Ruangsak; Teerapakpinyo, Chinachote (Asian Pacific Journal of Cancer Biology, 2019)
Aim: To identify the frequency of somatic BRCA mutation in epithelial ovarian cancer (EOC), particularly those with high grade subtypes. Methods: Patients diagnosed with EOC included fallopian tube cancer or peritoneal cancer who had surgery during January 2015 to December 2016 were included. High grade subtypes included high grade serous carcinoma, poorly differentiated endometrioid carcinoma, and clear cell carcinoma. BRCA1 and BRCA2 mutations were tested using DNA extracted from formalin-fixed paraffin embedded block or a fresh tumor specimen then analyzed by next generation sequencing system. Patients who had no germline BRCA mutation in their peripheral blood DNA investigated by bi-directional Sanger sequencing were diagnosed as having somatic BRCA mutation. Results: 36 patients were enrolled; majority of the patients (33patients; 97.2%) had EOC, 1 patient (2.8%) had fallopian tube cancer and 2 patients (5.6%) had peritoneal cancer. 28 patients (77.8%) had high grade serous carcinoma, 6 (16.7%) had poorly differentiated endometrioid carcinoma, and 2 (5.6%) had clear cell carcinoma. BRCA1 mutation was detected in tumor tissues of 2 patients (5.6%). These two patients had high grade serous carcinoma and significant family history of breast and/or ovarian cancers. However, BRCA1 mutations were detected in the peripheral blood in both of them. Conclusion: Only 5.6% of BRCA1 mutation was detected in ovarian tumor tissues, all mutations were found in high grade serous subtype. However, BRCA mutations were detected in the peripheral blood in both of them. Germline BRCA mutation was diagnosed, thus there were no somatic mutations in this study.